Two scenarios for sustainable welfare: New ideas for an eco-social contract - Ian Gough (European Trade Union Institute (ETUI), 2021)
More and more nation states are now committing to net-zero carbon by 2050 at the latest, which is encouraging, but none have faced up to the transformation of economies, societies and lives that this will entail. This paper considers two scenarios for sustainable welfare and discusses the implications for contemporary incomes, jobs and welfare states. It is necessarily restricted to the EU and similarly rich countries of the developed world. The first scenario is the Green New Deal framework to decarbonise the economy whilst addressing the distributional and welfare issues this would involve. This paper argues that expanded public provision of 'essentials' would be a necessary social component of this strategy. The second scenario goes further to counteract runaway private consumption by building an economy of egalitarian sufficiency with ceilings to income, wealth and consumption. This would require a further extension of labour market and welfare state interventions. The paper provides a framework for mapping and developing these two distinct approaches and for identifying a range of policy options on jobs and incomes.
Keywords: 330